Application of Sustainable Principles in Tower Buildings in Bali - Putrawan, I Gusti Ngurah; Rustiarini, Ni Wayan (Universitas Merdeka Pasuruan, 2025)
The study aims to examine the application of sustainable principles in tower development in Bali. With the increasing development of communication and tourism infrastructure, environmental sustainability has become a major challenge. This study uses a qualitative approach with a case study method on several towers that have implemented sustainability principles. The results of the study show that the use of environmentally friendly materials, energy efficiency, and harmony with local culture are the main factors in sustainable tower development in Bali. This study recommends improving regulations and incentives for companies that implement sustainable principles in infrastructure development. maximum 200 word abstract in English in italics with Times New Roman 10 point. Abstract should be clear, descriptive, and should provide a brief overview of the problem studied. Abstract topics include reasons for the selection or the importance of research topics, research methods and a summary of the results. Abstract should end with a comment about the importance of the results or conclusions brief.